Effect of caffeine supplementation on anaerobic power, time to exhaustion and exercise performance in martial arts girls - امیرحسین حقیقی; پروانه اصغری اردیزی; سید علیرضا حسینی کاخک (Shahid Beheshti University, 2011)
Purpose: The purpose of this study was to determine the effect of caffeine supplementation on anaerobic power, time to exhaustion and exercise performance in martial arts girls. Method: Thirteen martial arts girls (with the mean age: 21.46±2.78 years, height: 161±8.16 cm and weight: 52.54±7.17 kg) were selected voluntarily. In a crossover study design subjects were participated in three states: control, caffeine supplementation (5 mg٫kg) and placebo (starch powder as capsule). Then, subjects performed 30- s Wingate anaerobic test, maximal test (90% maximal heart rate) on treadmill for measuring time to exhaustion and martial simulated test for assessing exercise performance. The data were analyzed using repeated measures analysis of variance and Bonferroni post hoc tests. Results: The results showed that there was a significant increase (p<0.003) in time to exhaustion for the caffeine group compared to the control and placebo group. While, caffeine ingestion had no significant effect on anaerobic power and exercise performance. Conclusion: It can be concluded that martial arts girls can intake caffeine supplementation (5 mg٫kg) one hour prior to exercise for improving endurance but, additional research is needed to elucidate the effect of caffeine supplementation on anaerobic power and exercise performance